COLLABORATIVE ONLINE LEARNING (COIL) AS A PROMISING PEDAGOGY FOR ENGAGING STUDENTS IN GLOBAL COLLABORATION: UKRAINIAN-SPANISH CONTEXT - Viktoriia Drobotun; Tamara Kavytska; Inmaculada Fortanet-Gómez; Noelia Ruiz Madrid (Taras Shevchenko National University of Kyiv, 2023)
This paper gives insight into the theoretical and practical aspects of Collaborative Online International Learning (COIL) - a pedagogy that is fast emerging as a more democratic and dynamic alternative to traditional in-person student exchange programs. This pedagogy is currently gaining popularity among Ukrainian educators who are looking for new ways to engage students in international collaboration amid the emergencies of the ongoing war conflict in the country. The paper is a preliminary report of the research in progress which aims to investigate whether COIL can level the unevenly developed language and academic skills of the collaborating Spanish and Ukrainian students. The reported preliminary findings of one of the three collaboration projects carried out by the faculties of Taras Shevchenko National University of Kyiv (KNU) and Universitat Jaume I (UJI) show a range of benefits including academic skills enhancement, improvement of intercultural competence as well as personal satisfaction. The authors also shed light on the challenges encountered when introducing COIL activities into the classroom. Taken together, the article provides an insightful overview of the benefits and limitations of COIL strategies as a means of promoting intercultural and interdisciplinary learning and understanding.